Male Sex Is an Independent Predictor of Recurrence-Free Survival in Middle Eastern Papillary Thyroid Carcinoma - Siraj, Abdul K.; Parvathareddy, Sandeep Kumar; Annaiyappanaidu, Padmanaban; Siraj, Nabil; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2022)
Background: Disparity between sexes with regards to incidence, disease aggressiveness and prognosis has been documented in several cancers. Although various reports have documented the association between male sex and aggressive papillary thyroid carcinoma (PTC), the prognostic impact of sex on PTC has been inconsistent. The role of sex in PTC aggressiveness and outcome in Middle Eastern PTC remains unknown. Therefore, our study retrospectively analyzed the data of a large cohort of Middle Eastern PTC patients to address this issue. Methods: We compared men and women with respect to clinico-pathological characteristics, disease persistence, structural recurrence, risk stratification and prognosis. We included 1430 patient - 1085 (75.9%) women and 345 (24.1%) men. Results: The median follow up was 9.5 years. At diagnosis, 27% (93/345) of men were ≥ 55 years, compared with 17.8% (193/1085) of women (p = 0.0003). Men had significantly more advanced disease at presentation: higher stage (p = 0.0074), larger tumor size (p = 0.0069), higher rates of lymphovascular invasion (p = 0.0129), extrathyroidal extension (p = 0.0086), regional lymph node metastasis (p = 0.0279) and distant metastasis (p = 0.0101). There was a higher rate of recurrence (p < 0.0001) and TERT mutations (p = 0.0003) in male PTC patients than in female patients. Additionally, radioiodine refractoriness was higher in male PTC patients (p = 0.0014). In multivariate analysis, male sex was an independent prognostic factor for poor recurrence-free survival (RFS) (Hazard ratio = 1.58; 95% Confidence interval = 1.20 – 2.06; p = 0.0011). Conclusions: Men with PTC are more likely to present with more advanced and aggressive disease. Importantly, male sex was an independent prognostic factor for RFS. Thus, men may benefit from more aggressive management and therapeutic interventions.